Media Education as a Means of Sexting Prevention - Bielčiková , Kristína; Hollá , Katarína (Journal of Education Culture and Society, 2022)
Aim. The study aims to identify and compare the sending of own and somebody else’s intimate photos and videos and to point out the importance of media education as a meaningful way of preventing sexting. Methods. The research tool was an online self-designed questionnaire. 250 respondents aged 15 to 19 participated in the research. Results. The research has shown that sending their own photos and somebody else’s photos are equally frequent. Differences are only noticeable in average values. The findings offer an overview of sending sexually explicit photos and indicate decreased shyness, and a greater desire to attract attention through their own naked photos or videos. In the case of sending somebody else’s photos, it is a matter of ridiculing the victim without his/her consent. Conclusions. Primarily, the importance of media education ought to be pointed out, as it provides information about the dangers of publishing such photos and videos, and develops critical thinking and media literacy in children, which is key for the safeguarding of online space. We see the importance and significance of the study especially in the prevention of sexting through media education, which could be the primary means of eliminating it.